Meningitis aguda por streptococcus pneumoniae con líquido cefalorraquídeo normal - Vázquez, Jorge; Aducci, María; Méndez, Jorge; Godoy Monzón, Daniel; Gómez Paz, Rodrigo; Bruzzese, Karina; Jagger, Víctor (Revista del Hospital Italiano de Buenos Aires, 2010)
.